“God, Power and Money”¿Did Cosimo de’Medici Deceive Renaissance Florence? - Coppola, Salvatore (Universidad de Costa Rica, 2014)
The review addresses the personality of Cosimo de Medici in Renaissance Florence, which is torn between the personality of a business man or a humanist in the making.